Shall we double the box? - pitch scaling strategies for enhanced representativeness in soccer training - Deuker, A.; Wittkugel, J.; Jakobs, J.; Raabe, D.; Vogt, T. (International Journal of Sports Science & Coaching, 2025)
Purpose While UEFA soccer pitches have an area per player (APP) of 325m², Small-Sided Games (SSG) are commonly designed with an APP of approximately 150m², thus lacking spatial representativeness. We hypothesize that sub-tasks scaled by a match-derived APP more accurately simulate spatial full-size match conditions compared to prototypical conventional strategies and evaluate this empirically.